EVALUATION OF SOCIAL PROJECT: THERMODYNAMIC APPROACH - Назимко, Виктор Викторович; Пономаренко, Елена Викторовна; Гречко, Татьяна Константиновна (Eastern-European Journal of Enterprise Technologies, 2013)
This article substantiates method of quantifying the effectiveness of a social project on the basis of the thermodynamics of irreversible processes. Current methods do not enable us to reflect the aforenamed process as the mathematical relation which would be attended by all resources as relatively equal components. Application of the thermodynamic approach allows us to investigate the process of implementing the project or program by means of interaction (reaction) between resources which results in products of the project and attaining the ultimate objective. Interaction between resources is controlled by stoichiometric coefficients among all the resources of the project. This method can be applied in evaluating the effectiveness of social project characterized by absence of the explicit effect, high level of uncertainty of hypothetical result and difficulties with quantifying social effects of the project. Application of the thermodynamic approach enables researchers to compare all project resources and products in the quantitative aspect in the single mathematical model based on the well-developed apparatus of irreversible processes thermodynamics.